Natural Fibers Reinforcement of Denture base materials: Natural Wool Reinforcement (A Review of Literature) - Zahraa Abdulwahab Abdulrazzaq1 Bayan S. Khalaf 2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Heat-cured acrylic resin has been used to construct complete or partial edentulous denture bases for many years. However, it does not meet the ideal requirements of a dental prosthesis. Several researchers have studied the reinforcement of heat-cured acrylic resin with various fillers in order to enhance the properties of the acrylic. In this review of literature, the light will be concentrated on the role of natural fibers reinforcement with a focus on natural wool fibers.